Kampoeng Poerba Tourism Community: Preserving the Prehistoric Elephant Heritage at the Bumiayu Site - Fitriana, Kuntum; Priyadi, Sugeng (The Postgraduate School of Tourism Sahid Polytechnic, 2026)
This study aims to explore the history of ancient elephants at the Bumiayu Site and examine the role of the Pokdarwis Kampoeng Poerba in preserving and developing the potential of ancient heritage as educational and cultural tourism. Pokdarwis Kampoeng Poerba, located in Galuh Timur Village, Tonjong District, Brebes Regency, is a tourism organization at the Bumiayu Site. Through a historical approach with archaeological and anthropological approaches, this study traces the role of the local community in promoting the historical and cultural value of the site through the formation of Pokdarwis. The results of the study show that Pokdarwis plays a strategic role in reintroducing prehistoric heritage to the community through educational activities, tourism promotion based on local wisdom, and conservation efforts. These efforts not only strengthen the cultural identity of the local community but also open up opportunities for creative economy based on cultural heritage. This study recommends cross-institutional collaboration between the government, academics, and local communities to strengthen conservation strategies and the development of educational tourism at the Bumiayu Site.